PENGARUH PROJECT-BASED LEARNING (PBL) DENGAN MEDIA CANVA DAN LITERASI DIGITAL TERHADAP HASIL BELAJAR KOGNITIF IPAS SISWA KELAS V SEKOLAH DASAR - Devy Ruselvi; Jamaris Jamna; Maman Rumanta (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Education plays a crucial role in shaping a quality generation. However, observations conducted by the researcher on July 15, 2024, revealed that students’ learning outcomes in the Integrated Science and Social Studies (IPAS) subject were relatively low. The Recapitulation of Grade V IPAS Scores over the Past Three Years indicates that many students have not met the established Learning Achievement Criteria (KKTP) of 70. This condition suggests that students’ understanding of IPAS material remains suboptimal. This study employs the theory of basic education as the primary foundation for efforts to improve the quality of education in Indonesia. The research aims to analyze the effect of Project-Based Learning (PBL) assisted by Canva media and digital literacy on the learning outcomes of Grade V students in the IPAS subject. The study adopts a quantitative approach with a quasi-experimental design, specifically the Nonequivalent Control Group Design. The population consists of all Grade V students in Cluster II of Lubuk Basung District, with two classes selected purposively as samples. Data collection techniques include achievement tests, digital literacy questionnaires, observations, and documentation. Data were analyzed using a two-way ANOVA test with the aid of SPSS 16.0 software. The results show that the Project-Based Learning (PBL) model assisted by Canva is more effective in improving IPAS learning outcomes compared to conventional teaching methods. There is a significant influence of PBL assisted by Canva on students’ IPAS learning outcomes, a significant effect of digital literacy on IPAS achievement, and a significant interaction between PBL assisted by Canva and digital literacy in influencing IPAS learning outcomes. This study is limited to examining the effectiveness of PBL assisted by Canva and digital literacy in IPAS learning; however, these two factors may also be applicable to other subjects. Therefore, future research is encouraged to explore the effectiveness of this method across different learning areas.